2004
DOI: 10.1002/net.20002
|View full text |Cite
|
Sign up to set email alerts
|

Complete binary trees in folded and enhanced cubes

Abstract: It is well known that the complete binary tree B n (n ≥ 3) on 2 n ؊ 1 vertices is not embeddable into the n-dimensional hypercube. In this article, we describe a recursive technique to embed B n into the n-dimensional folded and enhanced cubes, if n satisfies certain necessary parity conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The embedding structure, such as linear arrays and rings, are suitable for designing simple algorithms with low communication costs. A large amount of efficient algorithms designed on the two fundamental networks for parallel and distributed computation to solve algebraic problems and graph problems can be found in previous works( [5], [6], [11]). These applications motivate us to study the embedding of Hamiltonian cycle on networks.…”
Section: Discussionmentioning
confidence: 99%
“…The embedding structure, such as linear arrays and rings, are suitable for designing simple algorithms with low communication costs. A large amount of efficient algorithms designed on the two fundamental networks for parallel and distributed computation to solve algebraic problems and graph problems can be found in previous works( [5], [6], [11]). These applications motivate us to study the embedding of Hamiltonian cycle on networks.…”
Section: Discussionmentioning
confidence: 99%
“…But the enhanced hypercubes are much more attractive than normal hypercubes due to its potential nice topological properties. For instance, in [1], S. A. choudum and R. Usha Nandini showed that a complete binary tree can be embedded in enhanced hypercubes Q n,k under some restricted conditions. Its special case of k = 1 is the wellknown Folded hypercube (denoted by F Q n ) which has received substantial researches ( [7], [12]).…”
Section: Introductionmentioning
confidence: 98%
“…Recently many variants of Q n have been proposed to improve the performance of Q n , and the most significant ones wielding a lot of influence are generalized hypercube, folded hypercube, twisted hypercube, argument hypercube and enhanced hypercube. ( [1], [6], [7], [12], [5], [4], [3], [9]). …”
Section: Introductionmentioning
confidence: 99%
“…For example, its diameter is n 2 , about half the diameter of Q n [5]; there are n + 1 internally disjoint paths of length at most n 2 + 1 between any pair of vertices [19]; there exists a cycle of every length l with n + 1 l 2 n − 1 if n is even [24]. Many results on folded hypercubes can be found in papers [3,5,6,8,9,11,12,19,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%